Application of Zero Waste Concept on Milkfish Shredded Meat Processing - Sakinah Haryati; Aris Munandar (JURNAL PERIKANAN DAN KELAUTAN, 2012)
Shredded meat milkfish is one of fishery products made from steamed milk fish meat, making meat, seasoning, frying and squeeze that will produce shredded meat. This study aimed to identification of the waste types and the application of the zero waste concept in the processing of milkfish shredded meat in Shefish business group located at Bumi Agung 1 Residence Serang Banten Province. In the process of making milk fish shredded meat waste is generated in the form of liquid and solid wastes. Liquid wastes include water fish washing results, steaming water and the juice of the fish meat. While the solid waste generated from the gills, guts, fish heads, skin and fins of fish, fish bones and condiments such as leather waste of onions and garlic skins. The application of zero waste concept through waste utilization optimizing the milkfish shredded meat processing can be done either on liquid and solid wastes. Utilization of liquid wastes such as water washing and boiling water containing soluble protein can be used as an ingredient in feed ducks pasta and flavor products. Utilization of solid wastes in the form of fish bones and spines can be used to fish bone meal, fish head waste can be processed into crackers calcium, and use of the intestines and gills can be used as raw fish silage or bekasang product. Milkfish skins and spins becomes to crispy product. Waste generated in the milkfish shredded meat processing of Shefish business groups are used yet. The application of zero waste concept by optimizing the utilization of waste is one of the effective and efficient solutions to prevent in the fish processing waste.Keywords: milkfish shredded meat, zero waste, waste, optimizing